The efficacy of interleukin‐1 antagonist drugs in combination with colchicine in patients with FMF‐AA with colchicine resistance after kidney transplantation: A study with histopathologic evidence. Issue 6 (13th April 2021) - Simsek, Cenk; Karatas, Murat; Tatar, Erhan; Yildirim, Ali Murat; Alkan, Funda Tasli; Uslu, Adam
Abstract: Background: The efficacy of anti‐interleukin‐1 (IL‐1) drugs in kidney transplant patients with FMF‐AA who developed colchicine resistance has not been clearly demonstrated. Method: Thirty nine kidney transplant recipients with FMF‐AA were evaluated. Group 1 consisted of patients who were in remission after transplantation with colchine and Group 2 included those who developed colchicine resistance. Results: The mean follow‐up of the patients was 88.5 ± 61.9 months. Following the treatment with IL‐1 antagonists; serum Amyloid A (SAA) averages (79.4 ± 35.3 mg/L) as well as the average number of hospitalizations per month due to FMF episodes (1.4 ± 0.5 times/month) decreased significantly (26.6 ± 25.9 mg/L and 0.1 ± 0.3 times/month) ( p  < .001). Rates of death with a functional graft were 30% and 0% in group 1 and 2 ( p  = .086). Biopsy‐proven AA amyloidosis recurrence in the allograft was observed in 11 of 19 (58%) and seven of nine (78%) patients in group 1 and 2, respectively. Interestingly, glomerular amyloid deposition was not present in the vast majority of biopsies. De novo vasculer amyloid deposition was observed during treatment. Conclusion: IL‐1 antagonist drug and colchicine combination almost completely prevented acute FMF attacks in kidney transplant patients with colchicine resistance. However, amyloid accumulation did not cease during IL‐1 antagonist drug treatment.